Fig 13-15; Kappa(T) measurements in the frame of a field study in Mozambique - Holger Preetz; Christian Rolf; Jan Igel (PANGAEA, 2020)
Purpose Electromagnetic induction based metal detectors are commonly used in landmine clearance operations.Their performance can be seriously deteriorated by magnetic properties of the soil in which the landmines are buried. Materials and methods Soil magnetic parameters were studied at three locations in Southern Mozambique where soils had caused severe problems during former landmine clearance campaigns. Field work comprised a geological and pedological survey of soils and the parent rock materials. Soil and rock samples were analyzed to determine pedological standard parameters and magnetic susceptibility. Geochemical analysis, scanning electron microscopy, and thermomagnetic analysis helped to clarify the Mineral composition and to specify the origin and properties of the magnetic minerals. The spatial distribution of the topsoil magnetic susceptibility was investigated in the field and characterized using geo-statistical analyses. Results and discussion Despite different degrees of weathering of the investigated soils, their magnetic mineral composition is dominated by lithogenic (Ti-) magnetites. Moreover, there are clues for the pedogenic neoformation of ultrafinegrained ferrimagnetic minerals in two of the three topsoils. The deterioration of metal detector performance at the sites results from the high frequency dependence of magnetic susceptibility at two locations and from the distinct spatial variability of topsoil magnetic susceptibility at all locations. Conclusions To assess soil effects on the performance of modern metal detectors the investigations of frequencydependent susceptibility and of spatial susceptibility distribution are the most meaningful tools. Summarizing, the topsoil magnetic properties of the investigated sites are predominantly influenced by their parentmaterial and to a minor degree by pedogenic neoformation.